1989
DOI: 10.1007/bf01067029
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting verdicts in cases where battered women kill their husbands.

Abstract: This study tested factors influencing verdicts in legal cases involving battered women who kill their husbands. A total of 388 college students (213 females and 175 males) read a fictitious but prototypical legal case. Subjects received one of three stories varying the level of force used by the husband against the wife before she killed him. Half of the subjects received courtroom testimony regarding the Battered Woman Syndrome. One-half received judge's instructions of not guilty by reason of selfdefense (NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 14 publications
8
55
4
Order By: Relevance
“…The written material, which included the defendant's testimony, other evidence and testimony, and judge's instructions, took approximately 20 to 25 minutes to read. The prototypical case of a battered woman experiencing long-term abuse in which a "good wife/mother" did her best to pacify her husband was used in the previous study by Follingstad et aL (1989). In the current effort; the woman's actions were varied along the lines of her behavior the night of the incident and her long-standing behavior within the marriage.…”
Section: Designmentioning
confidence: 98%
See 2 more Smart Citations
“…The written material, which included the defendant's testimony, other evidence and testimony, and judge's instructions, took approximately 20 to 25 minutes to read. The prototypical case of a battered woman experiencing long-term abuse in which a "good wife/mother" did her best to pacify her husband was used in the previous study by Follingstad et aL (1989). In the current effort; the woman's actions were varied along the lines of her behavior the night of the incident and her long-standing behavior within the marriage.…”
Section: Designmentioning
confidence: 98%
“…Testimony by an expert about the Battered Woman Syndrome (see Follingstad et aL, 1989) was included based on Schuller's (1992) findings that expert testimony regarding Battered Woman Syndrome as it applied to the defendant. The judge's instructions did not vary and were read by all subjects.…”
Section: Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Brekke and Borgida (1988) found that when two opposing experts on rape trauma syndrome presented evidence, mock jurors' responses were similar to the condition when no expert testimony was presented, suggesting that jurors may resolve the issue of conflicting testimonies by ignoring both of them (and resorting to their prior belief) or by accepting the one that supports their prior belief. Studies by Follingstad et al (1989) and Finkel, Meister, and Lightfoot (1991) reached a similar conclusion: Presence of an expert on battered woman syndrome did not alter the verdict reached by mock jurors in criminal cases, but it did influence the way jurors perceived the case. By contrast, Schuller's studies found that expert evidence altered jurors' evaluations of the defendant's perceptions and resulted in greater leniency in their verdicts (Schuller 1990;Schuller and Vidmar 1992).…”
Section: What Do We Know About Jurors' Reactions To Experts and Expermentioning
confidence: 79%
“…Common and legitimate explanations used to rationalize homicides committed by females include killing because of a mental illness, coercion, abuse, or self-defense (Follingstad et al, 1989;Vronsky, 2007). However, women have been perceived to be capable of committing only reactive or "expressive" violence-an uncontrollable release of pent-up rage or fear-and that they murder unwillingly and without premeditation.…”
Section: Red-collar Crime and The Female Offendermentioning
confidence: 99%